A dialectic of control and acceptance: Mealtimes with children on the autism spectrum. (1st October 2021) - Curtiss, S.L.; Ebata, A.T.
Abstract: Shared family meals have important implications for child health and wellbeing, however, mealtimes with children on the autism spectrum are often characterized by stress and problematic behavior. A better understanding of the underlying processes can elucidate the mealtimes challenges that families with children on the spectrum face as well as how families overcome those challenges in order to promote family health and wellbeing. Through a grounded theory analysis of mealtime observations, parent interviews, and child interviews with 16 families in the United States, we identified a theory of A Dialectic of Control and Acceptance. Integral to the role of mealtimes is for parents to express love through control and acceptance, however, these parallel processes are in tension with one another. How parents negotiate this tension dictates the degree to which their expectations are well aligned with their children's strengths and challenges and are able to provide effective support.